Design optimization and fabrication of a PCR reactor - Bosco, Monu. (2008)
DNA forms a building block of every living organism, but its scarcity for genetic testing, has hampered the capabilities of researchers. The problems was solved by the Nobel Prize wining discovery of PCR by Kary Mullis.